Validating the General Extended Technology Acceptance Model for E-Learning: Evidence From an Online English as a Foreign Language Course Amid COVID-19 - Jiang, Michael Yi-chao; Jong, Morris Siu-yung; Lau, Wilfred Wing-fat; Meng, Yan-li; Chai, Ching-sing; Chen, Mengyuan (Frontiers in Psychology, 2021)
The present work validated the general extended technology acceptance model for e-learning with survey data collected from an English as a foreign language online class during the novel coronavirus lockdown period. A total of 678 undergraduates participated in the survey. Structural equation modeling was employed to analyze the data. The results showed that the influence of students’ perceived usefulness on their intentional behavior to use the online learning system was not mediated by their attitude, indicating a very limited role of attitude towards technology in the model. Enjoyment and self-efficacy had no significant effects on the internal constructs, raising theoretical concerns on the applicability of this general model into specific contexts. In addition, we found that experience might be a moderator rather than an antecedent of the internal constructs in the model.